Case Report: Imaging and pathological analysis of intra-abdominal aggressive fibromatosis with abscess - Yang, Rong; Zhao, Juan; Zhou, Lin (Frontiers in Oncology, 2025)
This study investigates the imaging diagnosis and differential diagnosis of intra-abdominal aggressive fibromatosis (IAF) complicated by acute infection. Aggressive fibromatosis is a rare mesenchymal tumor of unclear etiology, potentially associated with genetic factors, hormonal levels, trauma, and other factors. Due to its clinical rarity and nonspecific imaging manifestations, preoperative diagnosis is challenging and prone to misdiagnosis, particularly in the more complex presentation of IAF. We present a rare case of IAF accompanied by abscess formation, analyzing its imaging and pathological features alongside clinical manifestations, and discuss diagnostic and therapeutic strategies.